Cover Picture: Total Synthesis and Biological Evaluation of (+)‐Gambieric Acid A and Its Analogues (Chem. Eur. J. 17/2013). Issue 17 (12th April 2013) - Ishigai, Kazuya; Fuwa, Haruhiko; Hashizume, Keisuke; Fukazawa, Ryo; Cho, Yuko; Yotsu‐Yamashita, Mari; Sasaki, Makoto
<x xml:space="preserve">Abstract</x> The first total synthesis of (+)‐gambieric acid A, a potent antifungal marine polycyclic ether, has been accomplished by H. Fuwa, M. Sasaki et al. in their Full Paper on page 5276 ff. in a convergent manner by relying on Suzuki–Miyaura reaction for the assembly of the A/BCD‐ and F′GHIJ‐ring fragments and a ring‐closing metathesis for formation of the nonacyclic backbone. The total synthesis unambiguously establishes the structure of this extraordinary complex molecule, thus demonstrating the important role of organic synthesis in the structural elucidation of natural products.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>